2021
DOI: 10.1093/mtomcs/mfab069
|View full text |Cite
|
Sign up to set email alerts
|

Structure, dynamics, and function of SrnR, a transcription factor for nickel-dependent gene expression

Abstract: Streptomyces griseus, a bacterium producing antibacterial drugs and featuring possible application in phytoremediation, expresses two metal-dependent superoxide dismutase (SOD) enzymes, containing either Fe(II) or Ni(II) in their active site. In particular, the alternative expression of the two proteins occurs in a metal-dependent mode, with the Fe(II)-enzyme gene (sodF) repressed at high intracellular Ni(II) concentrations by a two-component system (TCS). This complex involves two proteins, namely SgSrnR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Early work on ArsR family proteins suggested that the >3000 distinct members of this family were mostly metal ion or metalloid-specific regulators (6769). However, it has become increasingly clear that this is not the case (65, 70) as many recently described regulators have been shown to respond to reactive inorganic species (35, 40, 61) or may lack inducer binding sites altogether (7173). To understand the sequence relationships between these proteins and evaluate to what extent the differences in inducer recognition sites are captured in a large superfamily with low pairwise sequence conservation, we performed a sequence similarity network (SSN) analysis (74) of 168,163 unique entries from the Pfam PF01022 and Interpro IPR001845 datasets (13,879 sequences that are <50% identical over 80% of the sequence; UNIREF50 clusters).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work on ArsR family proteins suggested that the >3000 distinct members of this family were mostly metal ion or metalloid-specific regulators (6769). However, it has become increasingly clear that this is not the case (65, 70) as many recently described regulators have been shown to respond to reactive inorganic species (35, 40, 61) or may lack inducer binding sites altogether (7173). To understand the sequence relationships between these proteins and evaluate to what extent the differences in inducer recognition sites are captured in a large superfamily with low pairwise sequence conservation, we performed a sequence similarity network (SSN) analysis (74) of 168,163 unique entries from the Pfam PF01022 and Interpro IPR001845 datasets (13,879 sequences that are <50% identical over 80% of the sequence; UNIREF50 clusters).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1, in fact, contains the vast majority of described metalloregulators to date, that sense either biological transition metals, e.g ., Cu(I), Zn(II), Ni(II) or Co(II) and heavy metal xenobiotics Cd(II) and Pb(II) (subcluster 1B), or trivalent As(III)/Sb(III) (subcluster 1A). The exceptions are the sequences compiled in SSN cluster 21, representative of the Ni(II) sensor SrnR (73) and those in SSN cluster 22, representative of the Cd(II) sensor CmtR, with metal coordinating ligands derived from the DNA binding helix α4 (Figure S1B) (75, 76). Subcluster 1B contains all historically characterized, canonical As(III) sensors harboring a C-(V/A)-C motif that coordinates As(III), while cluster 5 includes many more recently described atypical As(III) sensors that feature trigonal Cys coordination with all metal ligands derived from α5 (Figure S1B) (77).…”
Section: Resultsmentioning
confidence: 99%
“…Early work on ArsR family proteins suggested that the >3000 distinct members of this family were mostly metal ion or metalloid-specific regulators ( 52 , 53 , 54 ). However, it has become increasingly clear that this is not the case ( 50 , 55 ) as many recently described regulators have been shown to respond to redox-active small molecules ( 20 , 24 , 46 ) or may lack inducer binding sites altogether ( 56 , 57 , 58 ). In order to evaluate these sequence relationships and the extent to which these differences in inducer recognition sites are captured in a large superfamily with low pairwise sequence conservation, we performed an SSN analysis ( 59 ) of 168,163 unique entries from the Pfam PF01022 and Interpro IPR001845 datasets (13,879 sequences that are <50% identical over 80% of the sequence; UNIREF50 clusters).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1, in fact, contains the vast majority of described metalloregulators to date, that sense either biological transition metals, for example, Cu(I), Zn(II), Ni(II), or Co(II) and heavy metal xenobiotics Cd(II) and Pb(II) (subcluster 1B) or trivalent As(III)/Sb(III) (subcluster 1A). The exceptions are the sequences compiled in SSN cluster 21, representative of the Ni(II) sensor SrnR ( 58 ) and those in SSN cluster 22, representative of the Cd(II) sensor CmtR, with metal coordinating ligands derived from the DNA-binding helix α4 ( Fig. S1 B ) ( 60 , 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is an exciting direction of future research, as the limit of microscopy techniques to identify these condensates has significantly improved in recent years, enabling us to find them even in bacteria where the size is usually close to the diffraction limit [159,169,170]. This is particularly relevant for bacterial transcriptional regulation, as many of these proteins contain intrinsically disordered regions IDRs [105,115,124,171,172] (Figure 3A,C,D,H-J), which is a common feature of proteins included in condensates [173][174][175].…”
Section: Simultaneous Functional and Structural Characterization On C...mentioning
confidence: 99%